OVARY DEVELOPMENT, FSH AND LH GENES EXPRESSION OF INDONESIAN LEAFFISH, Pristolepis grootii (Bleeker, 1852), INJECTED WITH LUTEINIZING HORMONE-RELEASING HORMONE ANALOG - Muslim Muslim; Agus Oman Sudrajat; Muhammad Zairin Jr.; Muhammad Agus Suprayudi; Arief Boediono; Iis Diatin; Alimuddin Alimuddin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Indonesian leaffish, Pristolepis grootii (Bleeker, 1852), is an undomesticated freshwater fish species native to the rivers, flooded swamps, and tributaries of Indonesia. The fish is mainly captured for consumption. In order to prevent its extinction and supply its growing demands, the artificial breeding of the fish should be developed. The purpose of this study was to determine the optimum dose of luteinizing hormone-releasing hormone analog (LHRHa) for stimulating the female P. grootii gonadal development at a dosage of 0, 1, 10, and 50 µg kg-1 of fish. Female fish (20.0 ± 0.6 g) were adapted for 30 days in the rearing environment and then separated into 12 aquariums with six fish per aquarium. Fish were then reared for another 21 days and fed with Tubifex sp. The LHRHa injection was conducted twice on day-7 and 14. Fish bodyweight, gonadosomatic index, gonad histology, blood estradiol-17â, and FSH-â and LH-â gene expression were evaluated at day 0, 7, 14, and 21. The results showed that the injection of the LHRHa hormone stimulated the development of fish gonads and was better achieved with a higher concentration of LHRHa. The best treatment was observed by the administration of 50 µg kg-1 of LHRHa that produced the fastest development among all treatments. This study demonstrated that the LHRHa induction could potentially stimulate the gonadal development of the newly domesticated fish. To our knowledge, this is the first study that reported the success of the induction of female gonad development in the Indonesian leaffish P. grooti.KEYWORDS: